1999
DOI: 10.1007/s000180050439
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial suicide through stress

Abstract: Outside of the laboratory, bacterial cells are constantly exposed to stressful conditions, and an ability to resist those stresses is essential to their survival. However, the degree of stress required to bring about cell death varies with growth phase, amongst other parameters. Exponential phase cells are significantly more sensitive to stress than stationary phase ones, and a novel hypothesis has recently been advanced to explain this difference in sensitivity, the suicide response. Essentially, the suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 23 publications
6
53
0
Order By: Relevance
“…This hypothesis is consistent with the suicide response model of Aldsworth and Dodd (1,21), which postulates that when actively growing cells are subjected to environmental stress, they produce an excess of free radicals inside cells. The model is supported by two recent studies which demonstrated that a set of common environmental response genes, which were up-regulated under a variety of stressful conditions, included representatives involved in defense against oxidative damage (11,27).…”
supporting
confidence: 87%
“…This hypothesis is consistent with the suicide response model of Aldsworth and Dodd (1,21), which postulates that when actively growing cells are subjected to environmental stress, they produce an excess of free radicals inside cells. The model is supported by two recent studies which demonstrated that a set of common environmental response genes, which were up-regulated under a variety of stressful conditions, included representatives involved in defense against oxidative damage (11,27).…”
supporting
confidence: 87%
“…Thus, it is thought that the two stressors may trigger similar responses. Though SOD is typically related to oxidative stress, in agreement with our results, SOD expression has been observed in E. coli cultures grown under high temperature conditions (Aldsworth et al, 1999). Because C. violaceum SOD is an iron-dependent enzyme, the observed increase in the expression of the ferrichrome-iron outer membrane receptor protein at high temperatures may account for the observed overexpression of SOD.…”
Section: Discussionsupporting
confidence: 91%
“…A competing idea on the cause of cyanobacterial cell death is based on the dependence of bacterial mortality on growth phase (Aldsworth et al, 1999;Mason et al, 1986). This concept, perhaps more familiar to phycologists, suggests that, when growth is arrested by some form of sublethal stress (e.g.…”
Section: Pcd In Bacteria Yeast and Eukaryotic Protistsmentioning
confidence: 99%
“…This concept, perhaps more familiar to phycologists, suggests that, when growth is arrested by some form of sublethal stress (e.g. nutrient limitation in culture), growth becomes uncoupled from metabolism, leading to cell death through an oxidative burst (Aldsworth et al, 1999). This idea has been used to explain cell death in cultures of phytoplanktonic Synechococcus (Sakamoto et al, 1998) and Synechocystis (Suginaka et al, 1999); metabolic imbalance (unbalanced growth) causes cell death, via unavoidable generation of oxidative stress.…”
Section: Pcd In Bacteria Yeast and Eukaryotic Protistsmentioning
confidence: 99%